2010
DOI: 10.5194/acp-10-2867-2010
|View full text |Cite
|
Sign up to set email alerts
|

The organic fraction of bubble-generated, accumulation mode Sea Spray Aerosol (SSA)

Abstract: Abstract. Recent studies have detected a dominant accumulation mode (∼100 nm) in the Sea Spray Aerosol (SSA) number distribution. There is evidence to suggest that particles in this mode are composed primarily of organics. To investigate this hypothesis we conducted experiments on NaCl, artificial SSA and natural SSA particles with a Volatility-Hygroscopicity-Tandem-DifferentialMobility-Analyser (VH-TDMA). NaCl particles were atomiser generated and a bubble generator was constructed to produce artificial and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 45 publications
2
70
0
Order By: Relevance
“…The organic fraction measured in PM 1 does fall within the observed range of 30-80 % organic mass fractions from sea spray aerosol studies Facchini et al, 2008;Keene et al, 2007); however, marine organic mass fractions as low as 4 % (8 % volume) have also been observed (Modini et al, 2010), and the relevant biogeochemical parameters of the seawater influencing the organic fraction of sea spray are still debatable.…”
Section: Correlations With Biogeochemical Parametersmentioning
confidence: 99%
“…The organic fraction measured in PM 1 does fall within the observed range of 30-80 % organic mass fractions from sea spray aerosol studies Facchini et al, 2008;Keene et al, 2007); however, marine organic mass fractions as low as 4 % (8 % volume) have also been observed (Modini et al, 2010), and the relevant biogeochemical parameters of the seawater influencing the organic fraction of sea spray are still debatable.…”
Section: Correlations With Biogeochemical Parametersmentioning
confidence: 99%
“…The mixing ratio of organic matter within the SS-OC type, due to its dominance in particles with D > 0.2 μm, exerts most of the organic mass variability in SSA overall. Prior studies have reported bulk organic mass fractions as high as 77-80% [Keene et al, 2007;Facchini et al, 2008] and as low as~4% [Modini et al, 2010] in SSA generated from natural seawater samples. The ensemble submicron organic mass fraction in these experiments was approximately 35-40% for periods Z1 and Z2 (Figure 6).…”
Section: Organic Mass Fractionmentioning
confidence: 99%
“…On the whole, the process of surfactant transport toward the air-sea interface would result in the accumulation of organic matter in the sea surface microlayer (SML) (Keene et al, 2007), which is a layer of material at the air-sea interface up to 1 mm thick that is typically highly enriched in dissolved and particulate organic material in the open ocean (Carlson, 1983;Liss and Duce, 1997;Aller et al, 2005;Cunliffe et al, 2011). Some sintered glass filter aerosol generators have been designed to mitigate the over-expression of organics in the SML by continuously refreshing the surface of the seawater subjected to bubbling (Keene et al, 2007;Modini et al, 2010;Bates et al, 2012); this design feature was not explicitly tested in this study. Wurl et al (2011) show that the SML exists on the ocean surface for wind speeds up to 10 m s −1 (global ocean mean wind speed is approximately 6 m s −1 ), so the existence of the SML is relevant for many instances of wave-induced bubble and foam production.…”
Section: Bubble-mediated Surfactant Transportmentioning
confidence: 99%
“…Recent reports indicate that pneumatic atomization does not produce particles of similar physical or chemical properties to those generated by bubble bursting (Fuentes et al, 2010b;Gaston et al, 2011). Until recently, two different bubble production techniques have been utilized for laboratory studies of aerosol composition: (1) air (or N 2 ) forced through sintered glass filters ("frits") (Cloke et al, 1991;Keene et al, 2007;Wise et al, 2009;Fuentes et al, 2010b;Modini et al, 2010;Park et al, 2014), and (2) impinging water jets (Facchini et al, 2008;Fuentes et al, 2010b;Hultin et al, 2010). A new approach introduced by produces SSA using reproducible breaking waves in a linear wave channel filled with natural, filtered seawater.…”
Section: Introductionmentioning
confidence: 99%